How Do You Solve For y In The Equation 2x + y = 6?
In the equation, 2x + y = 6 can be rearranged to solve for y.
Answer: Solving for y in the equation 2x + y = 6, we get y = 6 - 2x.
let us change the subject of the equation to y and find the solution.
To change the subject of the equation let us have y in LHS and transpose all the other terms to the RHS side.
To do this,
We can subtract 2x in both LHS and RHS
2x + y - 2x = 6 - 2x
Since 2x-2x = 0
We have y = 6 - 2x
Thus, Solving for y in the equation 2x + y = 6, we get y = 6 - 2x.